Arabidopsis ETHYLENE INSENSITIVE 3 directly regulates the expression of PG1β-like family genes in response to aluminum stress. (5th June 2022) - Jin, Jing; Essemine, Jemaa; Xu, Zhan; Duan, Jianli; Shan, Chi; Mei, Zhiling; Zhu, Jian; Cai, Weiming
Abstract : The Arabidopsis EIN3 transcription factor directly regulates the expression of PG1 β -like family genes to mediate ethylene-modulated pectin accumulation under aluminum stress. Abstract: The genes in the subfamily PG1 β ( beta subunit of poly-galacturonase isoenzyme 1) have a clear effect on the biosynthesis pathway of pectin, a main component of the cell wall. However, the detailed functions of the PG1 β -like gene members in Arabidopsis ( AtPG1 – 3 ) have not yet been determined. In this study, we investigated their functional roles in response to aluminum (Al) stress. Our results indicate that the PG1 β -like gene members are indeed involved in the Al-stress response and they can modulate its accumulation in roots to achieve optimum root elongation and hence better seedling growth. We found that transcription factor EIN3 (ETHYLENE INSENSITIVE 3) alters pectin metabolism and the EIN3 gene responds to Al stress to affect the pectin content in the root cell walls, leading to exacerbation of the inhibition of root growth, as reflected by the phenotypes of overexpressing lines. We determined that EIN3 can directly bind to the promoter regions of PG1 – 3, which act downstream of EIN3. Thus, our results show that EIN3 responds to Al stress in Arabidopsis directly through regulating the expression of PG1 – 3 . Hence, EIN3 mediates their functions by acting as a biomarker in their molecular biosynthesis pathways, and consequently orchestrates their biological network in response to Al stress.